DECONTAMINATION OF CONTAMINATED SCRAP METAL BY MELTING ARISEN FROM THE DECOMMISSIONING OF NUCLEAR POWER PLANT SHUT DOWN AFTER AN ACCIDENT - Slimák, Andrej; Necas, Vladimir (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
The paper briefly describes the decontamination of radioactive scrap metal by melting as prospective technology to reduce the amount of metallic radioactive waste. Decontamination by melting presents a particular advantage of homogenising a number of radionuclides in the ingots and concentrating other radionuclides in the slag and dust filter resulting from the melting process, thus decontaminating the primary material. Presented paper also deals with the evaluation of an exposure of the workers during melting of radioactive scrap metal as well as impact of melting on the environment. According to obtained results, the effective doses absorbed by workers during the melting meets legislatively given limit 20 mSv annually.